Assessment of Haematological Profile and CD4 Count of Patients with HIV Infection - Afreen Alam; Rakesh Jagat; Ram Singh Maniram; Bhawna Bhimte (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
Background and aim: Human Immunodeficiency Virus (HIV) infection is associated with morbidity and mortality worldwide. Anemia is the most common complication of HIV infection, which may be attributed to insufficient production of red blood cells. The present study was conducted to assess the hematological profile of HIV-positive patients irrespective of therapy and to establish a correlation with CD4 count. Material and methods: The present observational study was conducted at a tertiary care center in central India for two years, from June 2019 to June 2021. Clinical findings were noted, followed by hematological and CD4 investigations by flow cytometry. Results: Two hundred HIV-positive patients were enrolled; the mean age was 35.67±10.48 years. The majority of HIV patients, 80%, had anemia. Leukocytopenia and leukocytosis were documented in 10% and 7.5% of cases, and thrombocytopenia was noted in 22% of cases of HIV. About 49% of cases had a CD4 count of less than 200, and 40% of cases had a CD4 count in the range of 200 to 500. Statistically significant (P-value < 0.05) association of low CD4 count with loose motions, weight loss, pallor, anemia, neutrophilia, and low Mean corpuscular hemoglobin concentration (MCHC), were noted. Statistically significant (P-value < 0.05) positive CD4 counts with hemoglobin, lymphocytes, blood glucose, Mean corpuscular hemoglobin (MCH), and MCHC and a negative correlation with neutrophils were found. Conclusions: The study showed an association between hematological abnormalities in patients with HIV. CD4 counts are useful for staging and assessing the prognosis of patients with HIV infection.